Implementation of Digital Literacy in Learning at SMK Sore - Andhikasari, Rosiana; Novalia, Novalia; Emeilia, Rindana Intan; Muntazah, Arina (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
This study aims to describe the implementation of digital literacy in learning at SMK Sore. This research is a qualitative case study research. Data in this study is by observation, interviews, documentation, and artifacts. Data analysis in this research is the transcription and codification of interview and observation data, identification, and analysis of document data and artifacts. The results of this study show that implementing digital literacy in learning conducted by SMK Sore is very good for teachers, students, and schools and can also facilitate teaching and learning activities.